Measuring plaque in clinical trials: index or weight? - G. I. McCracken (journal of clinical periodontology, 2006)
Aim: To explore the possibility of using plaque weight rather than plaque index as a more objective, clinical outcome measure in periodontal clinical trials. Materials and methods: The study initially recruited 12 healthy volunteers who abstained from tooth cleaning for 24 h on each of the three occasions and then for 48 h on each of a further three occasions to accumulate plaque. On a further three visits, the subjects abstained from tooth cleaning for 24 h and then brushed with a powered toothbrush for 2 min. A split-mouth design with target teeth was adopted and plaque was first scored separately on each side of the mouth using the Turesky modification of the Quigley and Hein plaque index. Post-brushing residual plaque was also scored after tooth cleaning. Inter-proximal plaque was dried, removed, pooled and weighed: on one side of the mouth from the entire inter-proximal surfaces; and from beneath the contact points on the contra-lateral side. Results: Discriminant validity showed the index to have an advantage over weight in discerning between 24- and 48-h plaque deposits, and between 24-h plaque and postbrushing plaque. Test-retest validity confirmed that for repeated plaque growth, variability within subjects was greater than the variability between subjects. There was an association between plaque weight and plaque index although the regression lines were non-linear. Conclusion: There appears to be no significant advantage in using plaque weight in periodontal clinical trials.